2013
DOI: 10.1186/2193-1801-2-357
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases and hypersensitivities improve the prognosis in ER-negative breast cancer

Abstract: IntroductionBreast cancer (BC) is one of the leading causes of death among women worldwide. Immunostimulatory treatment has increasingly been used as adjuvant therapy in the last few years, in patients with melanoma and other cancer forms, often with an induction of autoimmunity as a consequence of a successful treatment. We aimed at investigating if coexisting autoimmune diseases (AD) or hypersensitivities (HS) similarly to the side effects of immunostimulatory treatment resulted in a better overall survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…In addition, around 30% of breast cancers are ER-negative tumors, with a higher proportion in young breast cancer patients, and these tumors constitute a subgroup with relatively poorer prognosis and fewer treatment options 34 - 36 . Our enrichment results showed a common theme of immune response across the three different methods; these findings that are consistent with previous results highlighting the importance of immune pathways in ER-negative breast cancer 37 - 39 .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, around 30% of breast cancers are ER-negative tumors, with a higher proportion in young breast cancer patients, and these tumors constitute a subgroup with relatively poorer prognosis and fewer treatment options 34 - 36 . Our enrichment results showed a common theme of immune response across the three different methods; these findings that are consistent with previous results highlighting the importance of immune pathways in ER-negative breast cancer 37 - 39 .…”
Section: Discussionsupporting
confidence: 92%
“…To determine appropriate intervention in this group of patients, it is therefore essential to perform a comprehensive baseline evaluation of musculoskeletal complaints. Our results are in conflict with those by Einefors et al, who showed improved BC outcome in patients with ADs [23]. Indeed, among the 1705 BC patients included in that analysis, those with coexisting AD (125 patients) had a not significant trend towards better OS, adjusted for age at diagnosis and TN stage (HR 0.91; CI 0.72–1.14).…”
Section: Discussioncontrasting
confidence: 99%
“…Prior studies have been inconsistent in demonstrating a definitive association between breast cancer aggressiveness and thyroid disease, particularly thyroid autoimmunity (1416). One study reported that patients with any type of thyroid disease (including hyperthyroid patients) were more likely to have a greater degree of lymph node involvement, a larger primary tumor, and vascular invasion, but there was no significant correlation with breast cancer stage or ER or PR status (17).…”
Section: Introductionmentioning
confidence: 99%